Biological process of lysine-tRNA charging is therapeutically targetable in liver cancer - Zhang, Ruyi; Noordam, Lisanne; Ou, Xumin; Ma, Buyun; Li, Yunlong; Das, Pronay; Shi, Shaojun; Liu, Jiaye; Wang, Ling; Li, Pengfei; Verstegen, Monique M. A.; Reddy, D. Srinivasa; et al. (Liver International, 2021)
Background & Aims Mature transfer RNAs (tRNA) charged with amino acids decode mRNA to synthesize proteins. Dysregulation of translational machineries has a fundamental impact on cancer biology. This study aims to map the tRNAome landscape in liver cancer patients and to explore potential therapeutic targets at the interface of charging amino acid with tRNA. Methods Resected tumour and paired tumour-free (TFL) tissues from hepatocellular carcinoma (HCC) patients (n = 69), and healthy liver tissues from organ transplant donors (n = 21), HCC cell lines, and cholangiocarcinoma (CC) patient-derived tumour organoids were used. Results The expression levels of different mature tRNAs were highly correlated and closely clustered within individual tissues, suggesting that different members of the tRNAome function cooperatively in protein translation. Interestingly, high expression of tRNA-Lys-CUU in HCC tumours was associated with more tumour recurrence (HR 1.1;P = .022) and worse patient survival (HR 1.1;P = .0037). The expression of Lysyl-tRNA Synthetase (KARS), the enzyme catalysing the charge of lysine to tRNA-Lys-CUU, was significantly upregulated in HCC tumour tissues compared to tumour-free liver tissues. In HCC cell lines, lysine deprivation, KARS knockdown or treatment with the KARS inhibitor cladosporin effectively inhibited overall cell growth, single cell-based colony formation and cell migration. This was mechanistically mediated by cell cycling arrest and induction of apoptosis. Finally, these inhibitory effects were confirmed in 3D cultured patient-derived CC organoids. Conclusions The biological process of charging tRNA-Lys-CUU with lysine sustains liver cancer cell growth and migration, and is clinically relevant in HCC patients. This process can be therapeutically targeted and represents an unexplored territory for developing novel treatment strategies against liver cancer.
Keywords: Cladosporin; liver cancer; lysine; Lysyl-tRNA Synthetase; tRNA-Lys-CUU; tRNAome